GLP‐1 could improve the similarity of IPCs and pancreatic beta cells in cellular ultrastructure and function. Issue 10 (16th August 2013) - Shi, Qiping; Luo, Simin; Jia, Haiying; Feng, Lie; Lu, Xiaohua; Zhou, Lixin; Cai, Jiye
ABSTRACT Transplantation of functional insulin‐producing cells (IPCs) provides a novel mode for insulin replacement, but is often accompanied by many undesirable side effects. Our previous studies suggested that IPCs could not mimic the physiological regulation of insulin secretion performed by pancreatic beta cells. To obtain a better method through which to acquire more similar IPCs, we compared the difference between IPCs of the GLP‐1 group and IPCs of the non‐GLP‐1 group in the morphological features in cellular level and physiological function. The levels of insulin secretion were measured by ELISA. The insulin and glucagon‐like peptide‐1 (GLP‐1) mRNA gene expression was determined by real‐time quantitative PCR. The morphological features were detected by atomic force microscopy (AFM) and laser confocal scanning microscopy (LCSM). Intracellular Ca2+ levels and Glucagon‐like peptide‐1 receptor (GLP‐1R) levels were determined by flow cytometer (FCM). We found that IPCs of the GLP‐1 group had bigger membrane particle size and average roughness (Ra) than IPCs of the non‐GLP‐1 group but still smaller than normal human pancreatic beta cells. The physiology function of IPCs of the GLP‐1 group were much closer to normal human pancreatic beta cells than IPCs of the non‐GLP‐1 group. GLP‐1 could improve the similarity of IPCs from human adipose tissue‐derived mesenchymal stem cells and pancreatic beta cells in cellular ultrastructure and function. J. Cell. Biochem. 114: 2221–2230, 2013. © 2013 Wiley Periodicals, Inc.